STUDENTS’ COMPETENCE IN USING DETERMINERS (THIS, THAT, THESE, THOSE) AT SMP NEGERI 2 KOTA TERNATE - Wahab, Lita; Aboe, Roswita M; Lestari, Sri Ayu Budi (Cakrawala Bahasa, 2025)
The purpose of this study was to determine students' competence in using determiner (This, that, these, those) in class VII students of SMPN 2 Kota Ternate in the 2025-2026 academic year. The population in this study were class VII students in the odd semester of SMPN 2 Kota Ternate in the 2025-2026 academic year. While the number of samples in this study was 30 respondents collected using purposive sampling. This study used a quantitative descriptive method. Data were collected using 30 multiple choice questions, matching and essays. The researcher found that no students were in the very poor category, four students (13.33 %) were in the poor category. Then there were seven students (23.33%) who were in the fair category, ten students (30.33%) were in the fairly good category, seven students (23.33%) were in the good category, one student (3.33%) was in the quite very good category, and one student (3.33%) was in the excellent category. In summary, the average score for students in using determiner (this, that, these, those) sentences was 69.4. This indicates that students' competence in using determiner (this, that, these, those) sentences in the even semester of seventh grade students is still fairly good.